Preparation and characterization of single crystalline In–Sn oxide nanowires. (July 2015) - Shi, Jen-Bin; Wu, Po-Feng; Lin, Ya-Ting; Chen, Chih-Jung; Kao, Chia-Tze; Lin, Hsien-Sheng; Lee, Hsuan-Wei; Liu, Hung-Hsin; Lee, Ming-Way; Chen, Chin-Yi; Young, San-Lin; Kao, Ming-Cheng; et al.
Abstract: Indium tin oxide (ITO; Indium oxide with tin doping) nanowires were first prepared via the electrochemical deposition and an oxidization method based on an AAO template. FE-SEM results show the synthesized ITO nanowires to have an approximate length of 8–10 μm with an aspect ratio close to 167. ITO nanowires with an In/Sn weight ratio of 8.8 (∼9:1) were observed from EDS. The crystal structure of ITO nanowires showed that all the peaks within the spectra can be indexed to In2 O3 with a cubic structure. The ITO nanowire is single-crystalline determined from selected area electron diffraction (SAED) patterns. An optical energy gap ( E g ) of the ITO nanowire is 3.8 eV. Highlights: Single-crystalline ITO nanowires have been synthesized by electrodeposition and an oxidization method. ITO nanowires have diameter of about 60 nm and length of 8–10 μm individually. ITO nanowires can be developed in gas sensor and solar cells.